PhET Simulation on Critical Thinking Skills of Preservice Elementary Teachers (PETs) in Science Learning - Nafisa Salsabila; Wuri Wuryandani; Bambang Saptono; Woro Sri Hastuti; Ahmad Syawaludin (Universitas Pendidikan Ganesha, 2024)
Current science learning still has limitations in discussion, information evaluation, and opportunities for in-depth practice, thus inhibiting the development of students' critical thinking skills. This study aims to explore the effect of PhET Simulation on the critical thinking skills of elementary school teacher candidates in science learning. PhET Simulation is an interactive media to support in-depth understanding and critical analysis of basic scientific concepts. This type of research is a quantitative Pre-Experimental study with a one-group pretest-posttest Design approach, involving 43 elementary school teacher candidates. Data collection was carried out through a critical thinking skills test, including indicators of interpretation, analysis, evaluation, explanation, and self-regulation, which were applied before and after treatment. The statistical analysis results show a significant increase in students' critical thinking skills scores after using PhET Simulation. The paired T-Test test showed a significant difference, and the N-Gain test obtained a score of 0.3765, categorizing the increase to a moderate level, indicating that this simulation is quite effective in improving critical thinking skills. The increase in critical thinking skill scores can also be seen in the average pretest score, which is 74.09, increasing to 83.51 in the posttest score. This finding confirms that PhET Simulation can be used effectively in science learning and supports the development of students' analytical skills. Thus, it can be concluded that PhET Simulation has a positive impact on science learning and has the potential to be an important learning medium in building students' critical thinking skills.